Diseño e implementación de un sistema automático de levantamiento de cárnicos para la molienda en la empresa don Toñito - Amaguaña Casa, Fausto Ezequiel (2019)
In this technological proposal the design and implementation of an automatic meat lifting system for milling was carried out at the company “Don Toñito”, starting from the problem that the company has in the process of lifting meat drawers from the ground to the grinding manually, generating an increase in time in due to the rest lapses of workers and therefore a loss in the production of the different types of sausages by the company. For the design of the meat lifting system, it originated from the need to lift a load ranging from 10 kg to 50 kg from the ground at a height of 1.05 m, parameters necessary for the grinding process, to determine the appropriate materials of the structure good manufacturing practice slate for processed foods was applied. This project was carried out by means of a hydraulic system to carry out tasks of lifting meat drawers towards grinding, for the selection of the elements used in the lifting system suitable materials for food handling was acquire, which are available in the local market. The implementation of the meat lifting system showed a 24.47% reduction in the production time of the various sausages, thus eliminating the duration of the worker's breaks after a lift cycle due to the they perform repeated actions, improving production in production of 34.76%.